Principales reacciones bioquímicas en el proceso de maduración del mango (Mangifera indica L.) - Murillo Chonana, Nayeli Yelitza (2023)
This document addressed the topic of the main biochemical reactions in the mango (Mangifera indica L.) ripening process. This fruit is one of the most important in the world, thanks to its sweet flavor, aroma, creamy texture and nutritional properties, which is also a climacteric fruit because it experiences a peak in respiration and ethylene production when it reaches the maximum degree of ripeness for consumption. The main objective was to determine the main biochemical reactions in the mango ripening process. An investigative methodology was proposed with a qualitative approach and a descriptive scope. In addition, to prepare this document, information was searched on websites, scientific articles and virtual libraries. The results obtained on the main biochemical reactions that take place during the mango ripening process have provided a deeper insight into the changes that occur in the fruit, from an immature state to a mature one. It was determined that the biochemical reactions are directed mainly towards the carbohydrates stored in the fruit. Starches, which represent a source of energy in the immature fruit, are degraded into soluble sugars, such as glucose and fructose. It was concluded that the main biochemical reactions that occur during the mango ripening process are mediated by key enzymes such as amylase and pectinase, whose activity increases as ripening progresses.